Analysis of symbolic meaning as an expression of Malay cultural values in the Malay ornaments of the Asserayah Al-Hasyimiyah palace, Siak Sri Indrapura Regency - Satria, Hengki; Kurniati , Fatia; Hadi , M Azam (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2024)
This study analyzes the Malay ornaments in the Asserayah Al-Hasyimiyah Palace, Siak Sri Indrapura Regency, to uncover their visual forms and symbolic meanings. A qualitative descriptive approach combined with semiotic methods was employed to understand these ornaments' artistic elements, functions, and cultural values. The findings reveal that the palace's ornaments feature various motifs, including flora (jasmine, ylang-ylang, roses), fauna (dragon heads), Arabic calligraphy, and geometric patterns. Each ornament carries symbolic meanings that reflect Malay cultural values, such as honesty (mangosteen tree), noble character (a cluster of garden flowers), and honor (wall crown). Beyond their decorative function, these ornaments also serve as a medium of visual communication that embodies Malay cultural identity. This study underscores the importance of preserving traditional ornaments as cultural heritage while enhancing public understanding of Malay art. These findings are relevant for supporting arts and cultural education and enriching studies on traditional architecture.